Diffuse large B cell lymphoma of submandibular gland in a seropositive case – a rare presentation - Binayke, Rachana S.; Deshpande, Kalpana A. (International Journal of Research in Medical Sciences, 2017)
Lymphomas account for 2%-5% of salivary gland neoplasms. The parotid gland is the most commonly involved, constituting 70% of the cases, followed by submandibular gland (25%), sublingual and minor salivary glands (<10%). In present study a 56 years old seropositive male presented with a submandibular gland swelling of 2 months duration; along with multiple cervical lymphadenopathy. Grossly a single, well encapsulated, grayish-white tissue measuring 3x2.5x2 cms was received. It was solid, grayish-white on cut section. Histology revealed features of diffuse large B cell lymphoma with myoepithelial sialadenitis. Immunohistochemistry showed positivity for LCA & CD20, thus confirming the histopathological diagnosis. Primary malignant lymphoma of salivary glands is uncommon. Inspite of malignant lymphoma being the second most common AIDS-associated neoplasm, it’s occurrence in submandibular gland is extremely rare.